How obesity impacts the skin microbiome - Literature review - Opalińska-Kubowicz, Marta; Popieralska, Kinga; Musialska, Zuzanna; Protsenko, Yuliia; Kowalska, Marta; Barczewska, Magdalena; Bieszczad, Dominika; Marczak, Anna; Stadnicka, Olga; Swojnóg, Marzena; Mazurek, Adam (Quality in Sport, 2026)
Background. Obesity is becoming an increasingly serious problem in society and affects an entire human body including skin. It potentially affects barrier integrity, immune responses and susceptibility to dermatoses. Aim. This review aims to examine how obesity changes the composition and function of the skin microbiome and what are the possible consequences. Material and methods. A research was performed in the PubMed and Google Scholar based on peer-reviewed studies published between 2017 – 2025 and focusing on phrases “skin microbiome”, “obesity”, and “skin diseases”. Results. Available studies indicate reduced microbial diversity, increased colonisation by opportunistic pathogens and overgrowth of yeasts on the skin of obese patients. Mechanical factors such as friction, sweating and elevated skin-fold temperature promote dysbiosis and inflammation. These changes are associated with dermatoses such as atopic dermatitis, intertrigo, folliculitis, seborrhoeic dermatitis and hidradenitis suppurativa. Treatment strategies include weight reduction, targeted skincare, antimicrobial treatment and new microbiome-modulating therapies. Conclusions. Obesity significantly influences the skin microbiome, contributing to a higher risk of infections and inflammatory dermatoses. Although the understanding of these mechanisms is improving, further research, particularly involving metagenomics and metabolomics is needed to develop more precise preventive and therapeutic approaches.